Worm-like micelles as a mobility control agent for chemical enhanced oil recovery - Kumar, S. (Society of Petroleum Engineers, 2015)
In this Paper, Wormlike Micellar (WLM) solutions were studied as an alternative to polymeric mobility control agent in chemical enhanced oil recovery. In which, two compositions of WLM solutions were chosen and prepared in laboratory - Hexadecyltrimethylammonium Bromide/Sodium Nitrate and Three-(N, N-Dimethyloctadecylammonio) Propane-Sulfonate/Sodium Dodecyl Sulfate (TDPS)/Sodium Chloride. Then following experiments were conducted - thermal stability test, rheological measurements to account the effects of concentration, shears rates, salinity (NaCl = 3.5 w/v, CaCl2 = 0.05 w/v and MgCl2 = 0.05 w/v), and temperature (30 to 70°C) on viscosity of these WLM solutions. Another stability test was conducted to test the effect of crude oil on WLM solution. The results showed that WLM solutions have excellent rheological resemblances with HPAM polymer solutions. On addition of salts, the WLM solutions were highly tolerant over entire range of shear rates. At 70°C, the thermal degradability of WLM solutions was less than HPAM polymer. Despite of all these significances viscosity of WLM solutions was deemed to the viscosity of water (1 cP) on mixing crude oil. It was due to strong interfacial activity between surfactants present in WLM compositions and crude oil. Such as, the IFT between crude oil and WLM solution was observed very low (0.3 to 0.55 mN/m) as compared to the typical system of water-oil (20 to 50 mN/m). Besides, core flooding was performed by mixed surfactant WLM solution (TDPS = 1.09 w/v, R = 0.55) at 70°C. The WLM solution produced an additional oil recovery of 10.9 beyond secondary recovery. Thus the results supported WLM solution to be potential mobility control for chemical EOR. Copyright 2015, Society of Petroleum Engineers.